POTENSI KOEKSPRESI CHIMERIC ANTIGEN RECEPTOR (CAR) DAN GEN FOXP3 PADA SEL T REGULATORS SEBAGAI MODALITAS TERAPI PENATALAKSANAAN AUTOIMUN - Khasanah, Yulia Cahya (Essential: Essence of Scientific Medical Journal; Vol 16 No 2 (2018): Volume 16 No. 2 (Juli-Desember) : Essence Of Scientific Medical Journal, 2019)
Introduction: Autoimmune disease is immune response that damages self-tissues and disrupts physiological functions of the body. The prevalence of autoimmune diseases has continued to increase globally since World War II. In US, this disease is the leading cause of death and commonly seen in women. Conventional autoimmune medicine suppresses most of immune system and causes patients to be more susceptible to opportunistic infections and cancer. Based on these facts, therapeutic innovations that are specific to pathological immune cells are needed. Molecular therapy using stable, target-specific Tregs engineered is potential as the latest modality for autoimmune therapy. Discussion: Autoimmune occurs when adaptive immune response attacks self-antigens. The autoimmune mechanism is then followed by activation of a large number of T cells. All activated T cells are controlled by T regulators or Tregs. Tregs have weaknesses which are low selectivity and stability. For this reason, Treg engineering with selective receptor expression and Treg stabilizer is needed. The selective receptors that can be modified with T cells are Chimeric Antigen Receptor (CAR). CAR is known to selectively inhibits pathological immune responses and stops inflammation. CAR is combined with Treg stabilizer which gives the effect of amplification and stabilization, that is Forkhead box P3 (FoxP3). FoxP3 is core protein that functions as the main regulator of Tregs development and self-tolerance. Conclusion:CAR/FoxP3-Engineered Tregs express FoxP3 that have strong affinity for self-antigens through CAR receptors. The application of CAR/FoxP3-Engineered Tregs increases the selectivity and stability of Treg cells to supress autoimmune.